(untitled) (Bangladesh Journal of Medicine, 2013)
Coronary heart disease is now one of the most common killer diseases in Bangladesh. . It is estimated that prevalence of the disease in the country is 6.8 million1 and day by day this alarming statistics is becoming worse. The causes of coronary heart disease is related to multiple risk factors and most common factors are high cholesterol and triglyceride rich food intake, lack of fresh vegetables and fruits in diet, tobacco abuse, obesity, physical inactivity, high blood pressure, diabetes, excessive stress in work etc. Among these risk factors dietary habit is one of the most important modifiable factors that can prevent coronary heart disease in various ways. By making some simple lifestyle intervention like increase the amount of dietary fibre intake can reduce the risk of getting coronary heart disease and as well as can also causes risk reduction for development of major coronary events like heart attacks. DOI: http://dx.doi.org/10.3329/bjmed.v21i2.13619 Bangladesh J Medicine 2010; 21: 96-100